MODELO DE CONTABILIDAD PARA LAS FARMACIAS, CASO PRÁCTICO FARMACIA PRINCIPAL JERUSALEN DE LA CIUDAD DE LOJA, PERÍODO 01 DE JULIO AL 31 DE DICIEMBRE DEL 2013 - Pacheco Poma, Wilman Patricio (2016)
The thesis work called "accounting model for pharmacies, CASE MAIN PHARMACY Jerusalem from the city of Loja, PERIOD 01 JULY TO 31 DECEMBER 2013" was developed by accounting procedures and applications that will contribute to the management of the owners of these businesses especially with the owner of the pharmacy JERUSALEM, who may know the current economic situation of the pharmaceutical companies, also using the Multiple Account System allow pharmacies to have your information in a more organized so they can optimize their management which will help decision making. The specific objectives are to establish the main and auxiliary documentation required by the accounting model to determine the accounting process and procedures that contribute to optimize the resources of the company, applying the accounting model in the main pharmacy Jerusalem, periodo01 June to 31 December 2013. The methodology used was the multiple account system where multiple accounts is used to record transactions relating to goods, which is advantageous because it allows to know the individual movement of each of these items. 5 The most relevant at the end of thesis conclusion is the importance of implementing the accounting model in the pharmacy and specifically on the Main Pharmacy Jerusalem, for the development of their business which allows to have real information, true and timely in its current economic situation will bring entrepreneurs in making decisions for higher profits and commercial development of the property.